BIBLIOMETRIC ANALYSIS OF THE WORKLOAD OF PHARMACY WORKERS IN PHARMACIES - Teguh Utama; Prasojo Pribadi; Seftika Sari (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2025)
In the face of digital changes, especially in pharmacies, workloads are becoming increasingly complex, influenced by technological advances, lifestyle changes, and work demands. The study aims to conduct a bibliometric analysis of literature related to the workload of pharmaceutical personnel in pharmacies. The research method used in the bibliometric analysis of workload research includes systematic steps to collect and analyze data from related scientific literature. The data collection technique is to search for research data results using the publish or perish 8 application by searching online for articles that have been published in journals registered with Google Scholar with the keyword "workload AND Pharmacist" from 2014-2024. The results of the bibliometric analysis provide an in-depth understanding of research trends in the workload of pharmaceutical personnel in pharmacies, dominant measurement methods, and significant contributions from researchers in this field. In addition, through network analysis, relationships and collaborations between researchers and research interdisciplinarity can be identified. The findings of this study provide valuable insights into recent developments in workload analysis. The conclusion of this bibliometric analysis shows that there has been no research on the workload of pharmaceutical personnel in pharmacies.